2006
DOI: 10.1128/jvi.00385-06
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Severe Acute Respiratory Syndrome Coronavirus Infectious cDNA Clone and a Replicon To Study Coronavirus RNA Synthesis

Abstract: The engineering of a full-length infectious cDNA clone and a functional replicon of the severe acute respiratory syndrome coronavirus (SARS-CoV) Urbani strain as bacterial artificial chromosomes (BACs) is described in this study. In this system, the viral RNA was expressed in the cell nucleus under the control of the cytomegalovirus promoter and further amplified in the cytoplasm by the viral replicase. Both the infectious clone and the replicon were fully stable in Escherichia coli. Using the SARS-CoV replico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
285
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(289 citation statements)
references
References 36 publications
2
285
2
Order By: Relevance
“…), but no differences in plaque size were seen in these mutants. Similarly, substitutions of an NendoU active-site His using SARS-CoV and HCoV-229E replicon systems 88,89 were tolerated but caused a reduction of viral RNAs when compared to cells carrying the wt replicon RNA (Hertzig T and Ziebuhr J, unpublished).…”
Section: The Role Of Nendou In Nidovirus Replicationmentioning
confidence: 97%
“…), but no differences in plaque size were seen in these mutants. Similarly, substitutions of an NendoU active-site His using SARS-CoV and HCoV-229E replicon systems 88,89 were tolerated but caused a reduction of viral RNAs when compared to cells carrying the wt replicon RNA (Hertzig T and Ziebuhr J, unpublished).…”
Section: The Role Of Nendou In Nidovirus Replicationmentioning
confidence: 97%
“…Indeed, cap methylation genes of many (ϩ)-RNA viruses, such as alphaviruses and flaviviruses, were shown to play a crucial role for efficient virus replication (20,24,(42)(43)(44). In the case of CoVs, a functional and genetic analysis performed on MHV temperature-sensitive mutants mapped to the N7-MTase domain of CoV nsp14 and in the 2ЈO-MTase nsp16 indicated that both are involved in positive strand RNA synthesis by previously formed replicase-transcriptase complexes (13).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of nsp14 N7-MTase and of nsp16 2ЈO-MTase in the capping pathway was recently demonstrated biochemically (1,18,20). Moreover, both nsp14 and -16 play crucial roles for efficient RNA synthesis within the SARS-CoV replicon and for transcription/replication of MHV-CoV (13,24).…”
mentioning
confidence: 99%
“…However recent advances in the stability of plasmid vectors and the availability of class II restriction endonucleases or restriction enzymes that cleave adjacent to the recognition sequence have circumvented some of these difficulties (43). The available clones and replicons (44)(45) have allowed many groups to readily investigate different aspects of the coronavirus lifecycle. Developments in the NMR field are also enabling the solution of larger RNA structures such as those that direct -1 PRF.…”
Section: Perspectivesmentioning
confidence: 99%